THE ROLE OF SOCIAL MEDIA IN FORMING BRAND IMAGE AND BRAND AWARENESS: HISTORICAL PERSPECTIVE FROM COFFEE SHOPS IN MEDAN CITY - Salsabil, Aisya; Prayogo, Rangga Restu (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This research explores the role of social media in forming brand image and brand awareness, with a focus on coffee shops in Medan City. Using a historical approach, this research looks at the evolution of coffee shop marketing from the traditional era to modern social media. Analysis was carried out on the marketing strategies used by coffee shops, including the use of visual aesthetics, authentic narratives and active interactions with customers. The research results show that social media plays a very important role in increasing brand awareness and strengthening relationships with customers. Nonetheless, challenges in online reputation management and the need to continuously innovate marketing strategies were also identified. The conclusion of this research confirms that social media has become an effective tool for coffee shops in Medan to build a strong and memorable brand image amidst increasingly fierce competition in the coffee industry.